Clinical characterization of HCC/CCA mixed cancers in a population-based cohort: original article - Teufel, Andreas; Rodriguez, Isaac; Winzler, Claudia; Kokh, Daria; Ebert, Matthias; Surovtsova, Irina; Morakis, Philipp (Journal of gastrointestinal and liver diseases, 2023)
Background and Aims: Primary liver cancer (PLC) ranks among of the most common cancers worldwide. Within this group, a minority of cases displays characteristics of both hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA), known as combined hepatocellular cholangiocarcinoma (cHCC- CCA). Currently, there is no specific standardized therapy for these mixed tumors. Therefore, the aim of our study was to analyze the clinical course, treatment and outcome of cHCC-CCA patients in a European population-based registry. - Methods: We investigated 9,144 patients with PLC (6,622 HCC, 2,356 iCCA, and 166 cHCC-CCA) diagnosed between 2009 and 2020. All data were obtained from Clinical Cancer Registry of Baden-Württemberg (BW), Germany. - Results: In all three groups patients were predominantly male (82%, 57%, and 68% for HCC, iCCA and cHCC-CCA groups, respectively). 48% of cHCC-CCA patients were diagnosed as stage IV cancers, which was more than for HCC (31%) but less compared to CCA (64%). Overall median survival of cHCC-CCA patients was worse compared to HCC (9-13 months vs. 15.5 months, p<0.001) and rather comparable to CCA (11.8 months). - Conclusions: Our data demonstrated that cHCC-CCA tumors appear to have a distinct clinical course with worse overall survival compared to HCC. Thus, identification of these cancers by histopathology is essential in order to further characterize this tumor entity and to provide accurate treatment to these patients.
Gesehen am 24.07.2024